Adherence to eye examination guidelines among individuals with diabetes: An analysis of linked health data. (20th August 2020) - Gibson, Alice A.; Humphries, Jacob; Gillies, Mark; Nassar, Natasha; Colagiuri, Stephen
Abstract: Importance: Screening for diabetic retinopathy for early detection and treatment can prevent vision loss. Background: We aimed to assess rates of eye examination of people with diabetes, adherence with national guidelines and investigate characteristics of those who do not adhere. Design: We used data from the 45 and Up Study, a cohort study of 267 153 randomly selected residents aged ≥45 years from New South Wales, Australia. Individual survey data collected in 2006 to 2009 were linked to corresponding national Medicare Benefits Schedule claims data for 2006 to 2016. Participants: The study sample included 24 832 participants who reported having diabetes and at least 5 years of observation. Methods: Claims for visits to optometrists or ophthalmologists were assessed to estimate rates of eye examination. Poisson regression models were used to investigate factors associated with non‐adherence. Main outcome measure: Participants were classified as adherent if the average time between eye care claims was consistent with national guideline of having an eye exam every 2 years. Results: Of 50% to 75% people with diabetes met the biennial eye examination guidelines and only 21% to 28% with diabetes duration ≥10 years were adherent to the annual eye examination guideline. Characteristics associated with greatest ( 1.3‐fold) risk of non‐adherence were smoking, age <60 years and higher income. Conclusions and relevance: There is a clear need to improve rates of adherence to eye examination guidelines among people with diabetes to reduce the personal and societal burden of diabetic retinopathy.